Administração remota de ambientes virtuais em rede para integração com sistemas de gerenciamento de aprendizado - Almendra, Camilo Camilo (2003)
Recently, the potential of the Internet as a low-cost means of communication and global reach has enabled a new form of distance learning. In that revolution, the learning management systems stand out, through which it is can manage the various aspects involved in the provision of courses away. Virtual reality has, in parallel to the evolution of distance education, experienced considerable expansion throughout the world, and has been highlighted by present several positive aspects for its use in education. One of the types promising applications are networked virtual environments, which, when allowing integration of virtual worlds and interaction of remote users in environments shared three-dimensional, open the prospect of being used in support of distance education. An integration of learning management systems and environments virtual network is therefore an interesting alternative for increasing the education programs at a distance. This integration enables various solutions already developed around the use of virtual reality to education can now be effectively made available more widely, through the wide base learning environments based on the Internet. In this paper, we present two important aspects of integration between virtual environments and network systems learning management, which are the management of real-time services and remote administration features. This observation led to the specification and modeling an interface for remote management of virtual environments network from learning management systems. Thus, we aimed to build a model easy integration to be incorporated and does not take into account specific aspects of internal architecture of each system type. As a case study, the interface set remote administration has been incorporated into a virtual environment facing network to education.